2010
DOI: 10.1007/s11239-010-0495-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative incidence of thrombosis in reported cases of deficiencies of factors of the contact phase of blood coagulation

Abstract: Thrombotic manifestations occurring in patients with coagulation defects have drawn considerable attention during the last decade. It concerned mainly patients with hemophilia, vW disease or FVII deficiency. Occasional reports involved also the deficiencies of the contact phase of blood coagulation, mainly FXII deficiency. The purpose of the present study was to evaluate the comparative incidence of thrombosis in all reported patients with FXII, Prekallikrein and Kininogens deficiencies. Out of the reported 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…There is scant data on a role for PKK in human thromboembolism. Only ϳ 75 cases for congenital PKK deficiency have been published, 7,8,29 precluding meaningful epidemiologic analysis, and an association between elevated PKK levels and thrombosis has not been established. 49 Small molecule inhibitors, antibodies and ASOs targeting fXI or fXIa are currently under development for therapeutic use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is scant data on a role for PKK in human thromboembolism. Only ϳ 75 cases for congenital PKK deficiency have been published, 7,8,29 precluding meaningful epidemiologic analysis, and an association between elevated PKK levels and thrombosis has not been established. 49 Small molecule inhibitors, antibodies and ASOs targeting fXI or fXIa are currently under development for therapeutic use.…”
Section: Discussionmentioning
confidence: 99%
“…Humans and other animals deficient in a contact activation protein are largely asymptomatic. 4,[6][7][8] However, the contact system may play an important role in thrombotic disease, as pharmacologic inhibition of fXIIa or ablation of the fXII or HK genes can protect mice from experimentally induced thrombosis in a variety of models. [9][10][11][12][13] Interestingly, fXII deficiency confers somewhat greater protection from thrombosis than fXI deficiency in some models, 11 implying that fXII may contribute to thrombus formation through additional pathways distinct from fXI-dependent intrinsic pathway activation.…”
Section: Introductionmentioning
confidence: 99%
“…10 Although fXII deficiency per se was considered to be a risk factor for VTE, 11 in retrospect, this conclusion was likely explained by reporting bias. Reevaluation of the reported cases 16 and extended fXII-deficient pedigrees 17 suggested that the majority of affected patients had other inherited or acquired risk factors that were more likely to explain the thrombotic events. In addition, it has been reported that a subset of antiphospholipid antibodies bind to fXII and may lead to an acquired "pseudo fXII deficiency" 18 ; these antibodies, rather than the measured fXII deficiency, may therefore account for the observed thrombotic events.…”
Section: Vte Fxiimentioning
confidence: 99%
“…32 Therefore, the available data on factor XII is much more limited compared with factor XI. In recent years, however, there is renewed interest in factor XII and its role in thrombosis.…”
Section: Factor XIImentioning
confidence: 99%